Effects of the internet on the spatial structure of innovation networks - Franz Tödtling; Alexander Kaufmann; Patrick Lehner (European Regional Science Association (ERSA), 2002)
Research on innovation systems and innovative milieux has shown that the innovation process of companies is strongly interrelated with other firms and organisations. Internet is a new information and communication technology with a considerable potential to change such relationships and networks. An often held expectation is that the Internet will allow firms to interact with distant partners more easily and that as a consequence innovation networks become independent from geographical space. A contrasting view argues that local and regional networks and innovation systems will keep their importance, due to the fact that tacit knowledge, face to face communication and institutional factors are still of key relevance. In the paper we are going to investigate to which extent and how the Internet changes innovation network of companies. Do firms using the Internet intensively have other innovation partners at wider spatial scales than firms which hardly use this communication technology? We have analysed the effects of the Internet on the innovation-related knowledge flows of firms by conducting a telephone survey, personal interviews and a WWW-survey of Austrian firms. Preliminary analysis shows that there is significant variance between firms depending on the relative importance of different types of knowledge communicated and the type of firm (e.g., science-based firms versus traditional manufacturing firms). Overall, there is evidence that the Internet made relations to innovation partners more efficient. However, the configuration of networks (types and location of partners) did not change as much as is often expected in the literature.
Keywords: 330